Determination of the circularity indicator in the forest sector according to the principles of the circular economy - Gayda, S.V. (Forestry, Forest, Paper and Woodworking Industry, 2023)
It is substantiated that the implementation of the circular economy in the forest sector is important and relevant, as it helps to preserve forest resources, contributing to the efficient use of materials and the reduction of wood residues, as well as the restoration and reuse of wood products. Analyzed and ranked according to the degree of importance of the principles of the hierarchy of 10R strategies of the circular economy in the forest sector in the form of a watering can, where the upper levels have a higher priority compared to the lower ones. The percentage of importance of each strategy according to the priority of actions of 10R strategies to achieve maximum circularity and sustainability was determined, in particular: Refuse (18.72%); Rethink (17.05%); Reduce (15.05%); Reuse (13.05); Repair (11.04%); Repurpose (9.03%); Remanufacturing (7.03%); Refurbish (5.02%); Recycle (3.01%); Recover (1.00%); Dispose (0.00 %). The state of the circular economy in the processes of logging, production of products from primary raw materials and processing of used (consumed) wood products in Ukraine was analyzed, which made it possible to determine the indicator of circularity in the forest sector. The method of determining the circularity index according to the 10R strategies of the circular economy for the three main components of the forest sector with the formation of three possible growth scenarios has been developed. The indicators of circularity for scenario No. 1 were determined, which characterize the 1st lowest level of efficiency for traditional technologies of utilization and useful use of wood resources with values for the processes: logging 6.02%, manufacturing of wood products 10.03%, processing of used wood 25, 09% Circularity indicators are calculated for scenario No. 2, which characterizes the 2nd middle level of efficiency, with emphasis on advanced technologies and business models based on the extension of the service life and life cycle of products with values for the processes: logging 26.09%, manufacturing of wood products 43.14%, processing of used wood 61.71%. Circularity indicators were calculated for scenario No. 3, characterizing a developed circular economy – the 3rd maximum level of efficiency, built on smart production and smart consumption with values for the processes: logging 43.15%, manufacturing of wood products 76.24%, recycling of used wood 93.15%. Possible weighted average indicators of circularity according to three scenarios were determined: No. 1, which characterizes the situation in the forest sector of Ukraine and is 13.71%; No. 2, which predicts the situation in the forest sector of Ukraine in the next 10-15 years at the level of 43.65%; No. 3, which predicts the situation in the forest sector of Ukraine in the perspective of 2050 at the level of 70.85%. Ways to increase the circularity index in the forest sector based on the principles of the circular economy, which include minimizing waste, optimizing the use of resources, and preserving natural capital, are outlined.